Correlation between knowledge of type II diabetes mellitus and glycaemic control - Hemlata; Sikka, Gitanjali; Shaveta; Meetu (International Journal of Research in Medical Sciences, 2024)
Effective glycemic control in type II diabetes mellitus (T2DM) is crucial but challenging, with patient knowledge playing a key role in successful management. Observational cross-sectional analytical study. A review of recent studies was conducted, focusing on the impact of diabetes knowledge on glycemic outcomes. There is a positive correlation between increased type II diabetes mellitus knowledge and improved glycemic control. Patients who had better disease knowledge of T2DM could effectively manage their disease condition, including regular monitoring and lifestyle changes, and had improved glycemic outcomes, while those with less knowledge had poorer control. Improving patient education is essential for better glycemic control in Type II diabetes mellitus. Healthcare systems should implement targeted educational programs to address knowledge gaps, especially in areas with limited healthcare access.